Lasers For Medical Applications : Diagnostics, Therapy And Surgery. - Jelinkova, H. (Elsevier Science, 2013)
Lasers have a wide and growing range of applications in medicine. Lasers for medical applications summarises the wealth of recent research on the principles, technologies and application of lasers in diagnostics, therapy and surgery. Part one gives an overview of the use of lasers in medicine, key principles of lasers and radiation interactions with tissue. To understand the wide diversity and therefore the large possible choice of these devices for a specific diagnosis or treatment, the respective types of the laser (solid state, gas, dye, and semiconductor) are reviewed in part two. P.- Resumé vydavatel
9.2 Methods of low coherence interferometry and optical coherence tomography.
Keywords: laserová medicína; laser medicine; elektronické knihy; sborníky; electronic books; papers of several authors